Molecular characterisation of the Her2-Top2A amplicon in breast cancer - Herd, Olivia Jayne (My University, 2010)
The HER2 gene is amplified in 20-30% of breast cancers, a common cancer amongst South African women. HER2 amplification is associated with a poor prognosis and predicts response to treatments such as Herceptin. The gold standard for HER2 testing is Fluorescent in situ Hybridisation (FISH) with dual colour probes for the HER2 gene and chromosome 17 centromere (CEP17) internal control. According to international guidelines, a HER2/CEP17 ratio >2.2 is considered positive. The HER2 FISH test is complicated by the emergence of ambiguous cases with increased CEP17 signals that cannot be accounted for by chromosome 17 polysomy (> 6 copies of CEP17) and that may hide true HER2 gene amplification. The aims of this study were to characterise the HER2 amplicon, in particular the copy number of genes in the vicinity of the HER2 gene, and to design an alternative control probe that could clarify the HER2 gene status in ambiguous cases. In addition, results on 1558 breast cancer specimens sent for routine testing were analysed to determine the trends of HER2 amplification amongst South African women. The rate of HER2 gene amplification was significantly higher (p < 0.05) in African patients (52%) than in Caucasian patients (43%). In Caucasian women, the rate of HER2 amplification in the younger group (68%) was significantly higher (p < 0.05) than in the general Caucasian group (43%), while the same was not seen in the African cohort. Nineteen ambiguous cases with more than 9 copies of CEP17 were further investigated. FISH assays with four different probe kits (PathVysion HER-2: Poseidon Repeat free TOP2A, HER2, CEP17: and Vysis PML-RARA respectively) were performed to determine the copy number of the HER2, TOP2A, RARA genes and CEP17. An in-house dual colour probe kit was designed using the ACTG1 gene as a control for HER2. Of the 19 ambiguous cases, 16 had centromeric amplification, showing that CEP17 is no longer an adequate internal control in FISH HER2 testing. The TOP2A gene was only amplified in HER2 positive cases and the RARA gene was only amplified when the TOP2A gene was also amplified. FISH with ACTG1 as v a control clearly revealed HER2 amplification in ambiguous cases on image analysis and gave HER2/ACTG1 ratios significantly higher than HER2/CEP17 ratios. However, screening of an additional 40 unambiguous cases showed an increased copy number, although limited ( 8), of the ACTG1 gene in four patients; this warrants further testing to assess the value of this gene as a control. Interestingly, a trend was observed for ACTG1 increased copy number in HER2 negative cases, this may point to the presence of a driver gene whose amplification tends to be mutually exclusive from HER2 amplification.
MSc (Med), Faculty of Health Sciences, University of the Witwatersrand
Keywords: breast cancer; Her2-Top2A amplicon